1996
DOI: 10.1089/jwh.1996.5.603
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Dysplasia Among Incarcerated Women: A Comparison of HIV-Seropositive and HIV-Seronegative Inmates

Abstract: The number of women in state and federal prisons more than tripled between 1980 and 1990. Among incarcerated populations, women have higher rates of human immunodeficiency virus (HIV) infection than men. HIV seroprevalence ranges from 2.1% to 16.1% for men and 2.5% to 25.8% for women in U.S. prisons. The objective of this study was to determine the prevalence of cervical dysplasia among HIV-seropositive and HIV-seronegative women in a prison population and to correlate Papanicolau (Pap) smear results with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…A study of women inmates in Rhode Island showed that 25% of HIV-seropositive inmates had squamous intraepithelial lesions. Cervical dysplasia was correlated with HIV seropositivity and, among HIV-infected women, with lower CD4 cell counts [12].…”
Section: Comorbid Conditions Of Hiv-infected Prison Inmatesmentioning
confidence: 93%
See 2 more Smart Citations
“…A study of women inmates in Rhode Island showed that 25% of HIV-seropositive inmates had squamous intraepithelial lesions. Cervical dysplasia was correlated with HIV seropositivity and, among HIV-infected women, with lower CD4 cell counts [12].…”
Section: Comorbid Conditions Of Hiv-infected Prison Inmatesmentioning
confidence: 93%
“…The latter 2 infections can lead to pelvic inflammatory disease. Trichomonas infection has been found to be highly prevalent among both HIVseropositive and HIV-seronegative women inmates in Rhode Island (45% and 43%, respectively) [12].…”
Section: Comorbid Conditions Of Hiv-infected Prison Inmatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of concern about the reliability of cytology readings, an independent pathologist reviewed these Pap smears. 11 The data on 41 women involved in the Prison Release Program during its first year were collected by chart review and from the computer database at the prison facility. 12…”
Section: Methodsmentioning
confidence: 99%
“…To aid the transition of HIV-positive women offenders into comprehensive care upon release, the Rhode Island Department of Corrections -in conjunction with the Rhode Island Department of Health, the Miriam Hospital and Brown University -has developed two programs that connect incarcerated HIV-infected women to community resources and continuity of HIV care (Cu-Uvin et al, 1996;Dixon et al, 1993;Flanigan et al, 1996;Kim et al, 1997;Skolnick, 1998). The limited geographic area and population of Rhode Island have facilitated the initiation of care within the prison, and then the follow-up upon release with the same health care workers.…”
Section: Linking Hiv-infected Incarcerated Women To Community Servicementioning
confidence: 99%